Latihan Birthball untuk Penurunan Nyeri Kala I Persalinan di Bidan Praktik Mandiri Juliana Tanjung Morawa - Eva Solena; Elvi Era Liesmayani; Riris Sitorus (Jurnal Kesehatan Cendikia Jenius, 2023)
Childbirth is the process of expelling the products of conception (fetus and placenta) through the birth canal with or without assistance after they have developed enough to live outside the womb (by their own strength). Labor pain is a natural reaction. The pain that will be felt is the same as the birth process. To find out the effect of birthball training on reducing pain in the first stage of labor in women giving birth before doing birthball training at the Juliana Tanjung Morawa Midwife Clinic. This research is quantitative using a quasi-experimental approach with a One Group Pre test and Post test design. Sampling used accidental sampling with a population of 30 respondents in accordance with exclusion and inclusion criteria. In this research, the instrument used was an observation sheet. The results of the statistical test obtained a p-value=0.000 (p<0.05) so it can be concluded that there is an effect of giving birthball exercises on reducing pain in the first stage of labor in mothers giving birth at the Juliana Tanjung Morawa Midwife Clinic in 2023.